Multimorbidity and lifestyle factors among adults with intellectual disabilities: a cross‐sectional analysis of a UK cohort. Issue 3 (28th November 2018) - Tyrer, F.; Dunkley, A. J.; Singh, J.; Kristunas, C.; Khunti, K.; Bhaumik, S.; Davies, M. J.; Yates, T. E.; Gray, L. J.
Abstract: Background: Multimorbidity [two or more conditions in addition to intellectual disability (ID)] is known to be more common among people with ID. However, the relationship between multimorbidity and lifestyle factors is currently unknown. The aim of this study was to determine the prevalence of multimorbidity in a population of adults with ID. We also aimed to identify risk factors, including lifestyle factors, for multimorbidity in this population. Methods: This was a cross‐sectional analysis using data from a diabetes screening study of 920 adults aged 18–74 years with ID living in Leicestershire, UK. We described comorbidities and the prevalence of multimorbidity in this population. We explored the relationship between multimorbidity and age, gender, ethnicity, severity of ID, socio‐economic status, physical activity, sedentary behaviour, fruit and vegetable consumption and smoking status using multiple logistic regression. Results: The prevalence of multimorbidity was 61.2% (95% CI 57.7–64.7). Multimorbidity was independently associated with being female ( P  < 0.001) and severe/profound ID ( P  = 0.004). Increasing age was of borderline significance ( P  = 0.06). Individuals who were physically inactive or sedentary were more likely to be multimorbid, independent of ability to walk, age, gender, severity of ID, ethnicity and socio‐economic status (adjusted OR = 1.91; 95% CI 1.23–2.97; P  = 0.004 and OR = 1.98; 95% CI 1.42–2.77; P  < 0.001). After excluding probable life‐long conditions (autism spectrum conditions, attention deficit hyperactivity disorders, epilepsy, cerebral palsy and other paralytic syndromes) as contributing comorbidities, the effect of sedentary behaviour, but not physical activity, remained ( P  = 0.004). We did not observe a relationship between multimorbidity, fruit and vegetable consumption and smoking status. Conclusions: Multimorbidity presents a significant burden to people with ID. Individuals who were physically inactive or sedentary were more likely to be multimorbid, but further work is recommended to explore the relationship between multimorbidity and lifestyle factors using standardised objective measures.